Relations among reinvestment, self-regulation, and perception of choking under pressure - Iwatsuki, T.; Van Raalte, J. L.; Brewer, B. W.; Petitpas, A.; Takahashi, M. (Journal of Human Kinetics, 2018)
The purpose of this study was to examine relations among reinvestment, self-regulation, and perception of choking under pressure in skilled tennis players. Participants were 160 collegiate players from the NCAA Division I in the U.S. and the 1st League in Japan. Participants completed questionnaires assessing reinvestment (conscious motor processing and movement self-consciousness), self-regulation, and perception of choking under pressure. Results of correlation analysis indicated self-regulatory factors were positively related to reinvestment conscious motor processing, but not with reinvestment movement self-consciousness. Self-efficacy and movement self-consciousness of reinvestment were found to predict one`s perception of choking under pressure. Results of simultaneous entry multiple regression revealed that tennis players who had low self-efficacy and were concerned about making a good impression with their movements were more likely to perceive that they choked during tennis matches. Additionally, Japanese players reported less self-regulation skills and a higher perception of choking under pressure than American players, suggesting the need for additional research on cross-cultural differences. Overall, these results suggest that self-efficacy may protect athletes from choking, but movement self-consciousness may lead athletes to choke during tennis games. Keywords: self-focus; metacognition; self-efficacy; collegiate athletes; cross-cultural comparison